(untitled) (Homoeopathy for All, 2025)
Autism spectrum disorder (ASD) is a set of neurodevelopmental disorders characterised by a deficit in social behaviours and nonverbal interactions, such as reduced eye contact, facial expression, and body gestures, in the first 3 years of life. It is not a single disorder, but rather a multi-factorial condition resulting from the interaction of genetic and non-genetic risk factors. Autism Spectrum Disorder is a multifaceted condition requiring early, comprehensive, and sustained intervention. While conventional approaches emphasise behaviour modification and pharmacotherapy for associated symptoms, homoeopathy offers a promising complementary role with individualised remedies addressing the child’s mental, emotional, and physical constitution. Future research should focus on integrating evidence-based alternative therapies with conventional modalities to improve the quality of life for individuals affected and their families.